Native CB1 receptor affinity, intrinsic activity and accumbens shell dopamine stimulant properties of third generation SPICE/K2 cannabinoids: BB-22, 5F-PB-22, 5F-AKB-48 and STS-135. (June 2016) - De Luca, Maria Antonietta; Castelli, M. Paola; Loi, Barbara; Porcu, Alessandra; Martorelli, Mariella; Miliano, Cristina; Kellett, Kathryn; Davidson, Colin; Stair, Jacqueline L.; Schifano, Fabrizio; Di Chiara, Gaetano
Abstract: In order to investigate the in vivo dopamine (DA) stimulant properties of selected 3rd generation Spice/K2 cannabinoids, BB-22, 5F-PB-22, 5F-AKB-48 and STS-135, their in vitro affinity and agonist potency at native rat and mice CB1 receptors was studied. The compounds bind with high affinity to CB1 receptors in rat cerebral cortex homogenates and stimulate CB1-induced [ 35 S]GTPγS binding with high potency and efficacy. BB-22 and 5F-PB-22 showed the lowest Ki of binding to CB1 receptors (0.11 and 0.13 nM), i.e., 30 and 26 times lower respectively than that of JWH-018 (3.38 nM), and a potency (EC50, 2.9 and 3.7 nM, respectively) and efficacy (Emax, 217% and 203%, respectively) as CB1 agonists higher than JWH-018 (EC50, 20.2 nM; Emax, 163%). 5F-AKB-48 and STS-135 had higher Ki for CB1 binding, higher EC50 and lower Emax as CB1 agonists than BB-22 and 5F-PB-22 but still comparatively more favourable than JWH-018. The agonist properties of all the compounds were abolished or drastically reduced by the CB1 antagonist/inverse agonist AM251 (0.1 μM). No activation of G-protein was observed in CB1-KO mice. BB-22 (0.003–0.01 mg/kg i.v.) increased dialysate DA in the accumbens shell but not in the core or in the medial prefrontal cortex, with a bell shaped dose–response curve and an effect at 0.01 mg/kg and a biphasic time-course. Systemic AM251 (1.0 mg/kg i.p.) completely prevented the stimulant effect of BB-22 on dialysate DA in the NAc shell. All the other compounds increased dialysate DA in the NAc shell at doses consistent with their in vitro affinity for CB1 receptors (5F-PB-22, 0.01 mg/kg; 5F-AKB-48, 0.1 mg/kg; STS-135, 0.15 mg/kg i.v.). 3rd generation cannabinoids can be even more potent and super-high CB1 receptor agonists compared to JWH-018. Future research will try to establish if these properties can explain the high toxicity and lethality associated with these compounds. Highlights: STS-135, 5F-AKB-48, BB-22, 5F-PB-22 are 3rd generation Spice/K2 synthetic cannabinoids. They are CB1 receptor ligands with higher affinity than JWH-018. They are CB1 agonists with higher potency and intrinsic activity than JWH-018. They increase NAc shell dopamine at doses consistent with their in vitro potency.